Construction of a Macrophage-Tropic Subtype C HIV-1-mGreenLantern Reporter Virus for Studies on HIV-1 Replication and the Impact of Methamphetamine - Dina Mofed; Angelo Mandarino; Xuhong Wu; Yuekun Lang; Anjali Gowripalan; Ganjam V. Kalpana; Vinayaka R. Prasad (Viruses)
HIV-1 subtype C viruses are responsible for 50% of global HIV burden. However, nearly all currently available reporter viruses widely used in HIV research are based on subtype B. We constructed and characterized a replication-competent HIV-1 subtype C reporter virus expressing mGreenLantern. mGreenLantern sequences were inserted in-frame with Nef ATG in HIV-1IndieC1. As controls, we employed HIV-1IndieC1, HIV-1ADA, and HIV-1NLAD8-GFP-Nef viruses. HIV-1IndieC1-mGreenLantern (HIV-1IndieC1-mGL) exhibited characteristics of the parental HIV-1IndieC1 virus, including its infectivity in TZMbl reporter cells and replication competence in macrophages. To further characterize HIV-1IndieC1-mGL virus, we tested its responsiveness to CCL2 levels, a characteristic feature of subtype B HIV-1 that is missing in subtype C. CCL2 immunodepletion inhibited the production of HIV-1ADA and HIV-1NLAD8-GFP-Nef as expected, but not that of HIV-1IndieC1-mGL, as previously reported. We also tested the effect of methamphetamine, as its effect is mediated by NF-kB and since subtype C viruses carry an additional copy of NF-kB. We found that methamphetamine increased the replication of all viruses tested in macrophages; however, its effect was much more robust for HIV-1IndieC1 and HIV-1IndieC1-mGL. Our studies established that HIV-1IndieC1-mGL retains all the characteristics of the parental HIV-1IndieC1 and can be a useful tool for HIV-1 subtype C investigations.